(untitled) (Canadian Oncology Today, 2024)
The human epidermal growth factor receptor 2 (HER2) is a member of the epidermal growth factor receptor (EGFR) family that initiates various signalling pathways that control cell proliferation and tumourigenesis. Historically, approximately 15% of breast cancers have been characterized by overexpression or amplification of HER2, known as “HER2+” breast cancers. This subtype has been associated with an adverse prognosis, along with a high risk of recurrence and worse survival outcomes. However, with the discovery and subsequent development of HER2‑targeted therapies, the clinical course of HER2+ breast cancers has fundamentally changed. Optimizing therapeutic strategies using existing and emerging HER2-targeted therapies to build upon these advances remains a major priority for clinical development and treatment delivery. In 1998, the American Food and Drug Administration (FDA) and Health Canada approved trastuzumab, the first HER2-targeted therapy. Trastuzumab, a monoclonal antibody that binds to the HER2 receptor, has demonstrated clinical activity and improved outcomes in patients with metastatic HER2+ breast cancer when combined with chemotherapy. Following soon after, the first trial of adjuvant trastuzumab (HERA) demonstrated improvements in outcomes when combined with chemotherapy for early HER2+ breast cancer. More than 25 years after its first approval, trastuzumab retains a central role in the treatment of both early and advanced HER2+ breast cancer and has provided a backbone for both new therapeutic combinations (eg. with small molecule inhibitors of HER2) and new classes of therapeutic agents (antibody drug conjugates [ADC]). These successors of trastuzumab are currently redefining the HER2+ treatment landscape in both advanced and early breast cancer.